1998
DOI: 10.1182/blood.v92.2.574.414k22_574_588
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Reverse Transcription-Polymerase Chain Reaction for Simultaneous Screening of 29 Translocations and Chromosomal Aberrations in Acute Leukemia

Abstract: We have developed a multiplex reverse transcription-polymerase chain reaction (RT-PCR) reaction, which enables us to detect 29 translocations/chromosomal aberrations in patients with acute lymphoid leukemia (ALL) and acute myeloid leukemia (AML). Through the construction and optimization of specific primers for each translocation, we have been able to reduce the set-up to 8 parallel multiplex PCR reactions, thus greatly decreasing the amount of work and reagents. We show the value of our set-up in a retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
114
2
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(122 citation statements)
references
References 60 publications
5
114
2
1
Order By: Relevance
“…The second major conclusion from our data pertains to the fact that the incidence of patients positive for fusion transcripts in both the AML (23%) and ALL (32%) subgroups is lower than in our retrospective analysis (Pallisgaard et al, 1998), where the incidence of patients positive for fusion transcripts were determined as 44 and 45% respectively. As the patient materials in the present and in our previous study (Pallisgaard et al, 1998) are not directly comparable, even larger studies are needed to corroborate this observation. Despite this, we feel that the unselected, prospective design of our study with no banking bias coupled with a molecular detection system, argue strongly for a re-evaluation of this important aspect of leukaemia diagnosis.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…The second major conclusion from our data pertains to the fact that the incidence of patients positive for fusion transcripts in both the AML (23%) and ALL (32%) subgroups is lower than in our retrospective analysis (Pallisgaard et al, 1998), where the incidence of patients positive for fusion transcripts were determined as 44 and 45% respectively. As the patient materials in the present and in our previous study (Pallisgaard et al, 1998) are not directly comparable, even larger studies are needed to corroborate this observation. Despite this, we feel that the unselected, prospective design of our study with no banking bias coupled with a molecular detection system, argue strongly for a re-evaluation of this important aspect of leukaemia diagnosis.…”
Section: Discussioncontrasting
confidence: 55%
“…Given the high number of balanced translocations described in leukaemia, some of which are very rare, and given that they can be used in detection of minimal residual disease (MRD) (Pallisgaard et al, 1999), we developed a multiplex reverse transcription (RT)-PCR that enables the detection of 27 lesions with nearly 80 fusion gene variants (Pallisgaard et al, 1998). The method was validated on archived material from over 150 AML and acute lymphoblastic leukaemia (ALL) patients, and found to be useful for identifying all translocation positive patients including a series of cytogenetically negative ones.…”
mentioning
confidence: 99%
“…Morphological diagnosis according to FAB classification, immunophenotype and cytogenetic analysis were performed locally. MLL gene rearrangement was determined by cytogenetic analysis and multiplex reverse transcription polymerase chain reaction (RT-PCR) analysis (Pallisgaard et al, 1998;Salto-Tellez et al, 2003) using the HemaVision kit (DNA Technology, Aarhus, Denmark). Southern blot or fluorescence in situ hybridization analysis was also performed in some patients.…”
Section: Patients and Samplesmentioning
confidence: 99%
“…However, individual RT-PCR for each fusion transcript is expensive and labor intensive. Pallisgaard et al (1998) has successfully demonstrated eight RT-PCR assays for screening of 29 chromosomal aberrations covering both common and uncommon fusion transcripts for childhood acute leukemia. In this study, we aimed to develop a simple RT-PCR method for the detection of the common and risk-stratifying chimeric transcripts in both childhood ALL and ANLL.…”
mentioning
confidence: 99%